Input modes and their effects on Iranian EFL learners’ incidental vocabulary learning - Muhammad Afsharrad; Fatemeh Molaei; Fatemeh Pourebrahim (Indonesian Journal of Applied Linguistics, 2023)
Incidental vocabulary learning has recently been the center of attention among the ways of vocabulary learning. In this field, the effect of input modes on incidental vocabulary learning has been investigated since last century; however, not much research has been dedicated to it in the context of Iran. This study investigates the possible effect of input modes on incidental vocabulary learning and tries to determine the extent to which each input mode contributes to incidental vocabulary learning. A sample of 89 young female Iranian students from English language institutes in Zanjan province was selected for this end. They were assigned to four groups, including three experimental groups and one control group. All the groups participated in a 14-day study procedure (three sessions), including Vocabulary Language Test , pretest, immediate posttest, and delayed posttest. The tests included a checklist and a multiple-choice test to measure the incidental vocabulary learning of participants. Several one-way ANOVAs were conducted to analyze the checklist and the multiple-choice test. The results indicated that the differences between input modes in terms of incidental vocabulary learning favored the Reading while Listening mode and, to a lesser degree, the Reading mode. However, only the Reading while Listening mode resulted in vocabulary retention. The data showed very little (almost no) advantage in favor of the Listening mode. These findings show that the purpose of vocabulary learning determines it means. That is, if learners aim at long-term retention, Reading while Listening better serves the purpose but both Reading and Reading while Listening result in short-term learning.